Islamophobia and the Representation of Islam and Muslims in the Western Media (Al Basirah, 2020)
The ethnic and Islamophobic trends were present in the westerndiscourses since long but they increased in number and intensity in the post9/11 scenario. The co-existence of Islamophobic trends in the Europeandiscourse did not only influence political and financial structures but alsothe social and cultural edifices. The paper attempts to analyze therepresentation of Muslims and Islam in the British media in the light of theavailable literature. The paper concluded that the British Muslims wereframed as alien “Others” by the British media. The portrayal of “others”was further linked to the racist notions of Islamophobia. The dominantthemes employed by the British press for the portrayal of Muslimsincluded „deviant‟, “immigrants”, “dangerous”, “problematic, and“oppressive”. The western media‟s tendency of frequently engaging theirown commentators for commenting on matters related to Islam andMuslims was considered as a main reason for biased representation ofIslam and Muslims in the Western media. Resultantly it is always “Us”which is representing “Them” instead of “They” representing“Themselves”. Thus the western media tends to portray Islam and West asopposites to each other.
Keywords: Islamophobia; Islam; Muslims; British Media; Us and Them.